1980
DOI: 10.1007/bf00427649
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tranylcypromine isomers on norepinephrine-H3 metabolism in rat brain

Abstract: The effects of d- and l-tranylcypromine on the disposition and metabolism of intracisternally administered l-norepinephrine-H3 were studied in rat brain. Both isomers inhibited the deamination of norepinephrine-H3. However, d-tranylcypromine was considerably more potent than the l-isomer in this respect. In addition, the l-isomer of tranylcypromine was found to enhance the disappearance of endogenous and tritiated norepinephrine from brain. Although this action appeared to result from an increase in catecholam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Results are expressed as percent inhibition of control (vehicle-treated) MAO-A activity (n = 4-8). TCP, which is structurally similar to amphetamine, has been reported to have effects on the uptake and release of catecholamines in brain tissue [Hendley and Snyder, 1968;Schildkraut, 1970;Baker et al, 1980Baker et al, , 1992Reigle et al, 1980], and it has been suggested that such actions may contribute to the antidepressant action [Hendley and Snyder, 1968;Reigle et al, 1980] and/or some of the cardiovascular side effects associated with TCP [Mallinger et al, 1986;Keck et al, 1991]. All values are significantly different from control values.…”
Section: Resultsmentioning
confidence: 99%
“…Results are expressed as percent inhibition of control (vehicle-treated) MAO-A activity (n = 4-8). TCP, which is structurally similar to amphetamine, has been reported to have effects on the uptake and release of catecholamines in brain tissue [Hendley and Snyder, 1968;Schildkraut, 1970;Baker et al, 1980Baker et al, , 1992Reigle et al, 1980], and it has been suggested that such actions may contribute to the antidepressant action [Hendley and Snyder, 1968;Reigle et al, 1980] and/or some of the cardiovascular side effects associated with TCP [Mallinger et al, 1986;Keck et al, 1991]. All values are significantly different from control values.…”
Section: Resultsmentioning
confidence: 99%
“…While racemic tranylcypromine is known to counteract behavioral effects of reserpine (Tedeschi, Tedeschi, Ames, Cook, Mattis, and Fellows, 1959), the present findings show reserpine-reversal to depend on pharmacological actions present in the (+)-isomer but absent in the (--)-isomer. Tranylcypromine stereoisomers have stereoselective effects on monoamine oxidase inhibition, monoamine uptake mechanisms and catecholamine release (Zirkle, Kaiser, Tedeschi, and Tedeschi, 1962;Horn and Snyder, 1972;Tuomisto, 1978;Reigle, Orsulak, Avni, Platz, and Schildkraut, 1980;Reynolds, Riederer, and Rausch, 1980), but it is unknown whether these actions can account fully for their stereoselective effects in reserpinized rats. Perhaps further studies on stereoselective pharmacological effects of tranylcypromine stereoisomers can clarify the molecular basis of reserpine-induced depression and of its reversal by psychoactive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Tranylcypromine stereoisomers [(+)-and (--)-trans-2-phenylcyclopropylamine] have stereoselective actions on monoaminergic mechanisms; the (+)-isomer [(+)-TCP] appears to influence mainly tryptaminergic mechanisms in addition to inhibition of monoamine oxidase, while the (--)-isomer [(--)-TCP] seems to act primarily on catecholaminergic mechanisms as an indirect agonist (see Smith, 1980;Reigle, Orsulak, Avni, Platz, and Schildkraut, 1980). The present study was carried out to investigate further the actions of tranylcypromine stereoisomers on monoaminergic neurotransmission using reserpine-reversal as the behavioral test.…”
mentioning
confidence: 99%
“…Previous studies have shown that the TCP enantiomers have markedly different pharmacological properties. (+)-R-TCP is a more effective M A 0 inhibitor, while ( -)-S-TCP is a better inhibitor of noradrenaline and dopamine uptake (Horn and Snyder, 1972;Fuentes et ul., 1976;Reigle et al, 1980;Reynolds et al, 1980;Hampson et al, 1986;Tuomisto and Smith, 1986). (+)-R-TCP has also been shown to increase levels of brain 5-hydroxytryptamine over those caused by the (-)-S-enantiomer (Smith and Peterson, 1982).…”
Section: Introductionmentioning
confidence: 95%